(untitled) (Global Journal of Medical Research, 2014)
The skin is a complex and the largest organ of the body. Because of complexity a wide range of diseases can occur in the skin, like tumors from surface epidermis, which is most exposed part to harsh environment and its pollutants. Diagnosis of any skin tumors can be done by correlating clinical features and histological features. This study "incidence of squamous cell carcinoma in Karnataka" was carried out for 18 months, from November 2005 to April 2007. 54 skin tumors were studied. Out of these 54 cases, 14 were diagnosed as benign tumors and 40 as malignant tumors. The malignant tumors constituted 74.07%.Skin tumors constitute a small but significant proportion of patients with cancer. Unlike in the Western countries, SCC is the commonest histological variety. In this century, the carcinogenic potential of both chemicals and radiation cannot be ignored.